Factors that influence the non-use of Open Fitness Zones in the city of Apucarana-PR - Morais, Josimar Florêncio de; Vieira-Souza, Lucio Marques; Dos Santos, Jymmys Lopes; Lima Júnior, Cássio Murilo Almeida; Costa, Frederico Barros; Da Silva, Fábio José Antônio (Journal of Health Care, 2021)
population, which have been implemented in Brazil since 2005, based on the Chinese model. In the city of Apucarana, Open Fitness Zones began to be implemented in 2006, and there are currently 42 of them. Objective: The present work aims to understand the factors by which the population of Apucarana uses Open Fitness Zones. Materials and Methods: A quantitative approach was used, whose data collection was carried out through the use of a semi-structured questionnaire containing closed questions applied to 384 people from neighborhoods where Open Fitness Zones are installed. Analyses and graphs were performed using the Epi Info â„¢ 7.2 software. Results: The reasons that led the population to use OFZ were: Health promotion (38.31%), Leisure (25.87%), Quality of life (20.40%), Aesthetics (7.46 %), Pleasure (4.48%), Others (2.49%), Social Interaction (1%). Conclusion: Public authorities should keep Open Fitness Zones in operation, as this type of policy is established in the long term, considering the significant number of users, as well as those who do not use them, but intend to use them in the future.